Big Data Analysis with Python : Combine Spark and Python to unlock the powers of parallel computing and machine learning /: Combine Spark and Python to unlock the powers of parallel computing and machine learning. (2019) - Marin, Ivan; Shukla, Ankit; VK, Sarang
No abstract available